2016
DOI: 10.12659/msm.897356
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Perfusion Computed Tomography in Carotid Endarterectomy: Initial Experience in 16 Cases

Abstract: BackgroundThis study aimed to evaluate the changes in perfusion computed tomography (PCT) parameters in carotid endarterectomy (CEA), and to discuss the use of intraoperative PCT in CEA.Material/MethodsSixteen patients with carotid stenosis who also underwent CEA with intraoperative CT were recruited in this study. We calculated quantitative data on cerebral blood flow (CBF), cerebral blood volume (CBV), time to peak (TTP), and the relative parameter values, including relative CBF (rCBF), relative CBV (rCBV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…A previous intraoperative study using MRI in patients undergoing EC-IC bypass was conducted by Wang et al 25 They concluded that this knowledge can help anticipate a hyperperfusion syndrome. Intraoperative data of cerebral blood flow changes after revascularization surgery were obtained with perfusion CT by Xue et al 26 in patients undergoing carotid endarterectomy. In comparison with perfusion CT scanning, MRI has the advantage of no ionizing radiation and less contrast-induced adverse reactions, as well as a higher spatial resolution, allowing for better detection of early and more-subtle hemodynamic changes.…”
Section: Alternative Novel Intraoperative Blood Flow Imaging Techniquesmentioning
confidence: 99%
“…A previous intraoperative study using MRI in patients undergoing EC-IC bypass was conducted by Wang et al 25 They concluded that this knowledge can help anticipate a hyperperfusion syndrome. Intraoperative data of cerebral blood flow changes after revascularization surgery were obtained with perfusion CT by Xue et al 26 in patients undergoing carotid endarterectomy. In comparison with perfusion CT scanning, MRI has the advantage of no ionizing radiation and less contrast-induced adverse reactions, as well as a higher spatial resolution, allowing for better detection of early and more-subtle hemodynamic changes.…”
Section: Alternative Novel Intraoperative Blood Flow Imaging Techniquesmentioning
confidence: 99%
“…Until now, the brain perfusion is mainly assessed in the clinic through the cerebral blood flow before and after the recanalization of vessels through thrombolysis, carotid angioplasty with stent placement, and/or carotid endarterectomy . Direct visualization of the collaterals remains in great need.…”
Section: Resultsmentioning
confidence: 99%